2014
DOI: 10.1152/ajpregu.00499.2013
|View full text |Cite
|
Sign up to set email alerts
|

Marinobufagenin regulates permeability and gene expression of brain endothelial cells

Abstract: Marinobufagenin (MBG) is a cardiotonic steroid that increases in the circulation in preeclampsia. Preeclampsia and eclampsia are associated with cerebral edema. Therefore, we examined the effects of MBG on human brain microvascular endothelial cells (HBMEC) in vitro. MBG enhanced the permeability of HBMEC monolayers at 1-, 10-, and 100-nM doses, but had no effect at 0.1 nM. Agilent Human Gene Expression microarrays were utilized in these studies. MBG treatment (10 nM for 12 h) downregulated concentrations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…The authors demonstrated that MBG could cause disruption of endothelial cell junction integrity, and this supports that MBG increases vascular permeability in endothelial cells for the first time. In addition, Ing et al [25] found that MBG enhanced the permeability of human brain microvascular endothelial cells (HBMECs). They also found that MBG could downregulate certain genes involved in adhesion in the endothelial monolayers obtained from the human brain.…”
Section: Introductionmentioning
confidence: 99%
“…The authors demonstrated that MBG could cause disruption of endothelial cell junction integrity, and this supports that MBG increases vascular permeability in endothelial cells for the first time. In addition, Ing et al [25] found that MBG enhanced the permeability of human brain microvascular endothelial cells (HBMECs). They also found that MBG could downregulate certain genes involved in adhesion in the endothelial monolayers obtained from the human brain.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma levels of MBG, but not EO, become elevated in patients with moderate PE [25]. In addition to the effects of MBG on Na + K + ATPase and fibrotic signaling, MBG has also been shown to interfere with the proliferation, migration, and invasion of cytotrophoblast (CTB) cells [26,27,28] and to disrupt endothelial cell junctions [29,30]. Recently, we demonstrated that CINO impedes Sw.71 CTB cell line function via cell cycle arrest and apoptotic signaling [31].…”
Section: Introductionmentioning
confidence: 99%
“…MBG levels are elevated in most PE patients. In vitro data demonstrate the effects of MBG on endothelial function [30] and cell growth [53] and, importantly, on proliferative and angiogenic signalling in CTB cells [26,27,28]. Compelling data from multiple animal models, in which MBG levels are elevated prior to the onset of preE, suggests that MBG may represent a relevant target for preE therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…TMEM207 expression is strictly regulated in human tissues and cells. TMEM207 mRNA is found in human kidney (36) and brain microvascular endothelial cells (37); low levels are found in other cells and tissues, except intestinal goblet cells (23, 38). …”
Section: Physiological Cellular and Tissue Expression And Biological mentioning
confidence: 99%